Characterization of pressure drop through two-stage particulate air filters. (2nd July 2020) - Jeon, Wonyoung; Lee, Byong Hyoek; Yun, Hyunjun; Kim, Jongcheol; Kang, Sanghyeon; Seo, Youngjin
Abstract : A common form of particulate air filters is the pleated filter. The pressure drop and particle removal efficiency are the most important performance indicators of this filter. A computational fluid dynamics (CFD) tool was utilized to predict the pressure drop of a two-stage filter cartridge. In the CFD analysis, the flow through the porous medium was used as an indicator of the pressure drop in the filter. The pressure drop of the two-stage filter was predicted through an experiment involving a single-stage filter at 1 m/s. The pleated filter cartridge size was 361 × 277 × 25 (L × W × H) mm 3 and the pitch of the pleats was 3.8 mm. Four classes of filters (E10, E11, E12, H13) were used in the experiments. The filter resistances of the four grades were estimated through the single-stage filter experiment, and the pressure drop of the two-stage filter was predicted at 0.5–1 m/s. To verify the predicted CFD analysis values, two-stage filters were fabricated and tested at 0.75 m/s. For the E12 + H13 combination filter, the analytical value was 111 Pa, which agreed with the experimental value of 109.9 Pa. The other filters exhibited an error of <2%.